2011
DOI: 10.1016/j.jeurceramsoc.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and crystalline phase formation during suspension plasma spraying of the alumina–zirconia composite

Abstract: Amorphous and crystalline phase formation during suspension plasma spraying of the alumina zirconia composite Tarasi, F.; Medraj, M.; Dolatabadi, A.; Oberste-Berghaus, Jorg; Moreau, C.Contact us / Contactez nous: nparc.cisti@nrc-cnrc.gc.ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…It was hypothesized that the dense alumina‐YSZ coating would tend to fail after a few thermal cycles due to the stresses induced at high temperatures generated by the crystallization of the amorphous phase in the ceramic. It should be stressed that the thermal cycles have been carried out at temperatures above the crystallization temperature of the amorphous phase in this composite, which is ~950°C . However, the stronger intersplat cohesion, as previously explained by McPherson, has supported the structure and prevented the visible delaminating of the coatings in the case of dense composite structure, irrespective of the large amorphous content in this coating.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…It was hypothesized that the dense alumina‐YSZ coating would tend to fail after a few thermal cycles due to the stresses induced at high temperatures generated by the crystallization of the amorphous phase in the ceramic. It should be stressed that the thermal cycles have been carried out at temperatures above the crystallization temperature of the amorphous phase in this composite, which is ~950°C . However, the stronger intersplat cohesion, as previously explained by McPherson, has supported the structure and prevented the visible delaminating of the coatings in the case of dense composite structure, irrespective of the large amorphous content in this coating.…”
Section: Resultsmentioning
confidence: 65%
“…Suspension plasma spray process was employed to produce dense and porous coatings using an axial injection plasma torch (Axial III; Northwest Mettech, North Vancouver, BC, Canada) of suspension into plasma jet, as per the details mentioned elsewhere . Two different powders were mixed to form pseudo‐eutectic composition of alumina‐8 wt% YSZ and were sprayed.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Such a high temperature combined with the high surface energy of nanosized composite particles results in the perfect melting and the formation of solid solution [20]. Tarasi [21][22][23] showed that crystalline structures of YSZ and Alumina present an exceptionally extended solubility of both components, especially Alumina into the Zirconia lattice. The lattice parameter studies suggest that the Al atoms possibly take the substitutional sites at low ratios and interstitial sites when higher amounts of Alumina are being dissolved in Zirconia.…”
Section: Hot Corrosion Test Resultsmentioning
confidence: 99%
“…Furthermore, the composite Al 2 O 3 -YSZ has shown the potential for amorphous phase formation as well. [17][18][19][20][21] In this study, we fabricated amorphous coatings of the near-eutectic composite Al 2 O 3 -YSZ using the air plasma spraying (APS) method. The microstructural characteristics of the amorphous coatings obtained under di®erent spraying conditions were investigated.…”
Section: Introductionmentioning
confidence: 99%